GEDE-GANG Sdn. Bhd. / Muhammad Farhan Mohd Fauzi ... [et al.] - Mohd Fauzi, Muhammad Farhan; Ismadi, Muhammad Azhad; Md Sukeri, Muhammad Syafiq; Ridzal, Muhammad Rafif Irfan; Zamzuri, Muhammad Zahidul Fitri
The business is based on a partnership where it consists of six members who hold key positions in the company such as General Manager, Administrative Manager, Marketing Manager, Operations Manager and Finance Manager. Flavored drink products are the main products we sell. Our company is located in Shah Alam with the address: 2-06-2, Blok 2, Presint Alami, Persiaran Akuatik, Seksyen 13, 40100 Shah Alam, Selangor GEDE-GANG SDN. BHD. is a Malaysian firm that specializes in the production of Flavored Water. Water is a necessary component of life. It boosts our self-esteem and makes us healthy. We all know that nearly 3/4 of the earth's surface is flooded. The same is true of the human body, with water accounting for 70% of its makeup. Humans can survive for more than a week without food but just a few days without water, according to studies. This emphasizes the importance of water in our lives and brings numerous benefits to our company, and we are convinced that our market can easily develop and spread throughout Malaysia. We decided to make some modifications by selling it in vending machines to make it trendier and more appealing. We all know that flavored beverages used to be offered in stores, but now that the stores can no longer be opened, the traders are losing money, and the customers are having a difficult time buying the drinks at this time. This will make it easier for all of us to buy drinks with the vending machine.